Financial Inclusion and Energy Poverty: A New Perspective on Transmission Channels Toward Sustainable Energy Access in Emerging Economies - Khan, Zeeshan (Curtin University, 2024)
Financial inclusion is pivotal for empowering nations to attain at least seven sustainable development goals. It holds paramount significance in addressing the pressing issue of energy poverty. Unlike past studies, this study aims to assess the influence of financial inclusion on energy poverty across a spectrum of representative emerging economies, including Brazil, China, Colombia, India, Indonesia, Malaysia, Mexico, the Philippines, South Africa, and Thailand.